A collection of abstracts: Faculty of Engineering / Universiti Teknologi MARA, UiTM - UiTM, Universiti Teknologi MARA (Faculty of Civil Engineering, UiTM, 2003)
The true strength of a Faculty is not reflected in the number of teaching staff or just on the physical facilities but more on the academic activities of the staff. Though teaching has been the main function of the academic staff at the Faculty of Civil Engineering, Universiti Teknologi MARA (UiTM), research activities were not neglected. Academic writings produced by the Faculty have been consistently presented at conferences and published in various journals during the years even when UiTM was known as Institut Teknologi MARA (ITM). Since acquiring University status, research activities at the Faculty have increased markedly. More papers are being presented and published. The Faculty felt that a proper record of papers produced should be kept, thus this collection of abstracts is intended to serve that purpose. Apart from that, it will also serve as a valuable reference for junior members of the Faculty not only for finding a starting point in doing research but also to get an insight of what the Faculty had achieved prior to their joining the Faculty.